International Conference on Acoustics, Speech, and Signal Processing
DOI: 10.1109/icassp.1989.267032
|View full text |Cite
|
Sign up to set email alerts
|

Non-parametric detection in underwater environments

Abstract: Motivated b y the recurring use of the generalized Gaussian family to model different underwater noise sources a n d t h e asymptotic performance levels of some commonly used detectors for this family, we examined the performance of these detectors for several different underwater noise sources. T h e sources considered are non-Gaussian, highly correlated, generally nonstationary, a n d vary from being lighter to heavier tailed t h a n Gaussian. Although t h e linear detector had t h e best performance, the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Letting be the signal, the signal strength and the noise, the observed data can be written as (3) Given the noise pdf of , a likelihood ratio function can be written as a function of the estimated signal strength (4) Maximizing the likelihood ratio , or equivalently, minimizing the negative log-likelihood ratio then gives us the best estimate of signal strength (5) The estimated signal strength is expected to be close to zero when no signal is present.…”
Section: A Maximum-likelihood Detectormentioning
confidence: 99%
See 1 more Smart Citation
“…Letting be the signal, the signal strength and the noise, the observed data can be written as (3) Given the noise pdf of , a likelihood ratio function can be written as a function of the estimated signal strength (4) Maximizing the likelihood ratio , or equivalently, minimizing the negative log-likelihood ratio then gives us the best estimate of signal strength (5) The estimated signal strength is expected to be close to zero when no signal is present.…”
Section: A Maximum-likelihood Detectormentioning
confidence: 99%
“…Nielsen and Thomas explored the use of nonparametric detectors in snapping shrimp noise [4], however, they concluded that the LC performed better than nonparametric techniques. This conclusion is not in agreement with the results obtained in this paper.…”
mentioning
confidence: 99%